When Panda came to our house - Jensen, Helen Zane. (New York : Dial Books for Young Readers, 1985)
A panda visits an American girl and teaches her about China.
School Library Journal.
Booklist.
Bulletin (Center for Children's books).
K-3
Keywords: Pandas -- Fiction; Pandas -- Fiction; Pandas -- Fiction; China -- Fiction; China -- Fiction; China -- Fiction